Geotechnical Frontiers 2017. selected papers from sessions of Geotechnical Frontiers 2017, March 12-15, 2017, Orlando, Florida - Brandon, Thomas L.; Valentine, Richard, J. (American Society of Civil Engineers, 2017)
Contains 54 peer-reviewed papers on wallls and slope stability and stabilization. Topics include: MSE retaining walls, rigid walls and nongravity walls, stabilization, and fiber optic and remote sensing.
Keywords: Walls -- Design and construction -- Congresses.; Slopes (Soil mechanics) -- Stability -- Congresses.; Geotechnical engineering -- Congresses.; elektronické knihy; electronic books